ICT Use, Competitive Pressures and Firm Performance in Mexico - Iacovone, Leonardo; Pereira-Lopez, Mariana; Schiffbauer, Marc (World Bank, Washington, DC, 2016)
This paper presents a set of stylized facts on the relation between information and communications technology (ICT) use, firm performance, and competition. Taking advantage of a novel firm-level data set on information and communications technology for Mexico, the study finds that firms facing higher competition appear to have more incentives to increase their use of information and communications technology. Accordingly, although there is indeed a positive relation between information and communications technology use and firm performance, this effect is greater for firms that face higher competition pressures, which is consistent with the theoretical predictions of the trade-induced technical change hypothesis.